Effect of Drying Temperature and Natural Fermentation on the Phytochemical Composition of Stinging Nettle Buds (Urtica parviflora) - Adhikari, Babita; Ale, Smriti (Himalayan Journal of Science and Technology, 2020)
Stinging nettle (Urtica parviflora), locally known as sisnu in Nepal, is rich in phytochemicals. Phytochemical are non-nutritive bioactive chemical compounds found naturally in plants; possess antioxidant activity and reduce the risk of different diseases by serving structural and functional role as well as an electrolyte. The effect of drying temperature (50, 60, 70ºC) and natural fermentation (24±1ºC for 15 days) of fresh nettle buds on the phytochemical composition (polyphenol, tannin, flavonoid and antioxidant activity) were studied. The phytochemical screening of the samples was carried out using 80% ethanol through maceration technique. The tannin, flavonoid, total phenol content and antioxidant activity in ethanolic extract of fresh nettle buds were found to be 1.02±0.08 mg/g, 0.126±0.005 mg/g, 145.69±2.01 mg/g and 59.53±0.03% on dry basis respectively. The increase in drying temperature, significantly (p<0.5) decreased the polyphenol contents but had no significantly effect on the tannin, flavonoid content and antioxidant activity. The DPPH radical scavenging activity of leaves dried at 50ºC was found to be maximum (56.72±0.07% on db) and minimum (47.56±0.02%) at 70ºC. The natural fermentation significantly (p<0.05) increased the total phenol (273.2±2.33 mg/g), flavonoid (0.408±0.08 mg/g) and tannin (3.56±0.11 mg/g) content on dry basis. The increase in total phenol and flavonoid content exhibited the subsequent increment in the antioxidant activity (87.69±0.02%). It was found that, nettle buds contained a number of health promoting bioactive compounds such as tannins, polyphenol and flavonoid and their concentration increased significantly by natural fermentation but were not significantly affected by drying temperature (50-70ºC).